1961
DOI: 10.1001/jama.1961.03040130016004
|View full text |Cite
|
Sign up to set email alerts
|

The Renal Transport of Nitrofurantoin

Abstract: The mechanism of excretion of nitrofurantoin in the kidney was studied in anesthetized dogs by direct collection of urine from ureteral catheters. The method of stop flow analysis, involving a period of occlusion of the ureter, was applied in order to determine in which part of the nephron nitrofurantoin is excreted; in addition, simultaneous nitrofurantoin and creatinine clearance determinations were performed on four dogs at varying levels of urinary pH and plasma CO2 combining power. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1964
1964
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…The mechanisms leading to DILI are not completely clear, and severe fatalities due to hepatic toxicity have been reported for NFT. Animal PK studies have indicated that NFT kinetics are not linearly proportional to the administered dose [ 12 , 17 , 19 ]. At the same time, human PK exhibits high variability [ 2 , 29 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms leading to DILI are not completely clear, and severe fatalities due to hepatic toxicity have been reported for NFT. Animal PK studies have indicated that NFT kinetics are not linearly proportional to the administered dose [ 12 , 17 , 19 ]. At the same time, human PK exhibits high variability [ 2 , 29 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study has shown that a minimum of 30% of the administered dose needs to reach the urinary bladder to obtain an optimal therapeutic effect. Animal studies have shown that the pharmacokinetics of NFT exhibits dose-dependent and non-linear kinetics, especially in the urine [ 17 , 18 , 19 ]. Additionally, human studies have shown that urine PK and plasma PK are highly variable between subjects [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…although comparable cotransporters are found in various tissues [90], Amiloride is secreted by the proximal tubule [ 12] to reach concentrations which will be high enough to inhibit the apical sodium channel only in the distal nephron. The selec tive urinary anti-infectious effect of nitrofu rantoin [150] occurs by the same mechanism. The selective renal tissue removal of heavy metals by the organic anion complexing agent 2, 3-dimercapto-l-propanesulfonate may be explained by its selective concentration in the nephron after secretion through the organic anion system [132], Luminal presence is nec essary for action of uricosuric drugs like pro benecid and sulfinpyrazone [40].…”
Section: Influence O F Organic Ion Secretion On Rena! Functionmentioning
confidence: 95%
“…(3) Renal excretion depending on filtra tion and active secretion, with little reabsorplion: this is seen for numerous substances, like the anions p-aminohippurate [18], and the cations tetraethylammonium [104], N 1-methylnicotinamide [109], cimetidine [81,103], and mepiperphenidol [17], (4) Renal excretion depending on filtra tion and passive reabsorption, with no secre tory movement: this is the case for paraceta mol [34], and phénobarbital [142], (5) Renal excretion involving filtration, active secretion and passive reabsorption: this would be the pattern of excretion of the cations methadone [7] and quinine [ 135], and for the anions phenybutazone [47], and nitro furantoin [150]. The case of salicylate is not clear, since active reabsorption has been pos tulated to explain part of its rcabsorptive movement [106], (6) Renal excretion after filtration, active secretion, and passive and active reabsorp tion: pyrazinoatc [40,94], w-hydroxybenzoate [77], ascorbate [76], and pantothenate [68] follow this pattern of excretion.…”
Section: Different Patterns Of Renal Excretion Of Xenobioticsmentioning
confidence: 99%
“…Even though nitrofurantoin does not produce effective blood levels after therapeutic doses (7), the assumption that this drug posesses antibacterial activity in kidney tissue could be based on the following observations. (i) Stop-flow data indicate that this agent is reabsorbed in the distal tubule and possibly in the adjacent portion of the proximal tubule (1).…”
Section: Action Of Nitrofurantoinmentioning
confidence: 99%